2021
DOI: 10.9734/jpri/2021/v33i44b32705
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Percussive Massage versus Calf Stretching on Pain, Range of Motion, Muscle Strength and Functional Outcomes in Patients with Plantar Fasciitis – A Research Protocol

Abstract: Introduction: Plantar fasciitis occurs with the deterioration of the plantar fascia and related surrounding tissues around the heel's medial calcaneal tuberosity. This illness usually causes tightness in the calf muscles. These tight muscles are thought to interfere with the normal biomechanics of ambulation. The invention of percussion massage guns intends to improve the usefulness and efficiency of self-myofascial release, following in the footsteps of vibrating foam rollers. Since there is limited research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Stretch the gastrocnemius and soleus by hanging a towel on your foot and pulling it toward your body while in a seated position. Each set will consist of 15 s of exercise, with five sets in total, and a rest time of 5 s between each set [38].…”
Section: Calf Musclesmentioning
confidence: 99%
“…Stretch the gastrocnemius and soleus by hanging a towel on your foot and pulling it toward your body while in a seated position. Each set will consist of 15 s of exercise, with five sets in total, and a rest time of 5 s between each set [38].…”
Section: Calf Musclesmentioning
confidence: 99%
“…Similarly, the three most effective treatment protocols for individuals afflicted with PF (mobilization and manipulation of the foot and ankle, PF cross friction massage and stretching of the gastroc-soleus complex) were compared. Cross friction massage and gastrosoleus stretching were determined as the most effective treatment protocol for PF, Rama (2012) and using massage as a rehabilitation method in PF patients will help patients (Lakhwani and Phansopkar, 2021). However, when the relevant literature is examined, it is observed that there are conflicting results that DFM is effective in PF patients.…”
Section: Dıscussıon and Conclusıonsmentioning
confidence: 99%
“…Using a percussion massage gun releases tension and promotes flexibility while also by triggering a calming reaction and stimulating the Golgi tendon organ, it can enhance blood flow and the supply of nutrients to the tissue. Furthermore, by utilizing pain gait theory, it lessens the impression of pain 10 .…”
Section: Introductionmentioning
confidence: 99%